Grenada. Significant achievements 2016 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Granada during 2016 are identified, with respect to the needs and interests of the country, strengthening issues such as public policies, technology, packaging, production, trade, governance, composting, food safety, good agricultural practices , risk control, resilience against climate change, health and safety. Likewise, work was done on the use of pesticides, on the selection and treatment of fruits, on coconut plants resistant to diseases, on improving the quality of bananas, on the control and prevention of pests and diseases. Finally, support was given to combating bad post-harvest practices, the use of rainwater and the use of pesticides.